Comparative constitutionalism in South Asia - Khilnani, Sunil (ed.) (New Delhi, 2013)
This pioneering volume maps out the intellectual and historical contours of this little-studied field, yet one that is critical to South Asia's future, the mutual borrowing, citing and dialogue across the constitutional jurisdictions of South Asia. This nascent but significant development provides the basis, the volume argues, for a distinct comparative constitutionalism focused on the South Asian region. The essays collected here examine whether the experience so far of comparative law across South Asia offers insight into broader trends in constitutionalism and also ask how the corpus of general comparative constitutional law might benefit from greater familiarity with the South Asian experience.
Keywords: "South aAsia, Constitutional law, Comparative law, Khilna"